THE EFFECT OF NUTRITIONAL STATUS AND TNF ALPHA TO LUNG FUNCTION ON MARBLE CRAFTSMAN (Jurnal Teknologi (Sciences & Engineering), 2024)
Marble craftsmen are potentially exposed to marble dust which contains about 60% silica resulting in marble craftsmen facing this hazard and possibly physiological lung disorders. In addition, this hazard will increase Tumor Necrosis Factor-a (TNF- α) levels. This study aims to analyze the effect of working period, nutritional status, and TNF-α on physiological lung disorders. study is a quantitative study with observational research type and cross sectional research design In this study, the data collection techniques used were: (1) measurement of personal river stone dust levels using a personal dust sampler of CCZG2A type; (2) measurement of serum TNF-α levels using the ELISA technique, (3) examination of lung function with MIR spirolab III; (4) collection of data on respiratory complaints using the ATS standard questionnaire as well as to obtain data on age, tenure, length of work and smoking habits; (5) measurement of nutritional status by weighing body weight and measuring height. The data obtained were then presented in the form of tables, narratives, analyzed using statistical programs. The subjects of this study were all marble craftsmen who worked in the marble household industry in Tulungagung Regency as many as 30 people with the number of samples taken as many as 26 craftsmen. The average value of %FVC in obese respondents was lower than that of respondents with normal nutritional status. This indicates a decrease in lung function conditions in obese workers.